Southeast Asian Regionalism: An Examination of the Progress and Priorities of ASEAN through its Joint Communiqués - Velasco, Joseph Ching (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
In pursuit of ASEAN’s objective to formalize the ASEAN Community, this article critically examines the community-building progress and the organization’s key priorities. The research is guided by two research problems. First, what are the subjects discussed in each ASEAN community pillar? Second, how are the key issues addressed in relation to each ASEAN community pillar? A thematic analysis of the joint communiqués published by ASEAN from 2004-2019 was conducted to respond to these questions. More specifically, each communiqué was tagged and analyzed, and themes were subsequently derived, enabling a comprehensive examination of each area of the ASEAN community. The article contributes significant insights into the evolving landscape of ASEAN’s cooperation and integration. The findings elucidate on the shifting dynamics and complexities that shape ASEAN’s political-security, economic, and socio-cultural communities, shedding light on the organization’s changing priorities and challenges. The ASEAN Economic Community (AEC) prioritizes key growth areas, such as tourism, Small and Medium Enterprises (SMEs), and energy. For the ASEAN political-security, its focus is on ascertaining continued peace in the region as exemplified by collaboration on non-traditional security issues. Meanwhile, the ASEAN socio-cultural community primarily centers on environmental issues, disaster response and management, and the youth. However, the advancement of the ASEAN community has faced setbacks caused by the COVID-19 pandemic and the 2021 Myanmar coup d’état. Overall, the joint communiqués manifests the different initiatives that ASEAN has taken to deepen integration and a sense of community.